THE RELATIONSHIP BETWEEN MOTHER'S KNOWLEDGE AND HUSBAND'S SUPPORT WITH STUNTING PREVENTION BEHAVIOR IN GAMPONG CEURIH, ULEE KARENG SUB-DISTRICT, BANDA ACEH CITY - komala (Aceh Sanitation Journal, 2023)
Stunting begins when the fetus is still in the womb caused by the mother's food intake during pregnancy which is less nutritious. As a result, the nutrition that the child gets in the womb is insufficient. Malnutrition will inhibit the growth of the baby and can continue after birth. Stunting in children can be caused by various factors, one of which is low parental knowledge regarding normal child development and family support, especially husbands for pregnant women, which is needed in care during pregnancy. the support provided can affect the success of the mother in fulfilling the mother's nutrition during pregnancy. The purpose of this study was to determine the relationship between the mother's knowledge and the husband's support with stunting prevention behavior in pregnant women in Ceurih Village. This type of research is an analytic observational study using a cross-sectional research design. Samples taken as many as 38 pregnant women in the first, second, and third trimesters who were in Gampong Ceurih were taken by total sampling technique. data was collected through interviews guided by a questionnaire. The results of the bivariate analysis using Chi Square found a significant relationship between the knowledge of pregnant women and stunting prevention behavior in Ceurih Village with a p-value (0.001) and there was a significant relationship between the support of pregnant women's husbands and stunting prevention behavior with a p-value (0.005 ).